Asset and Liability Strategy: Its Impact on Profitability and Firm Value - Putri, Hana Tamara; Masyhuri, Muhammad Ade (Universitas Batanghari Jambi, 2025)
This study aims to analyze and provide empirical evidence regarding the effect of asset and debt management policies on firm value, mediated by profitability, in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study population consisted of 34 healthcare companies listed on the IDX, using a purposive sampling technique that resulted in 10 companies as samples based on certain criteria. The results show that total assets and total debt, both simultaneously and partially, have a significant influence on profitability, as measured by net income. Furthermore, these financial policies also significantly influence firm value, as influenced by price-to-book value (PBV), both directly and indirectly. Net income has a positive and significant effect on PBV, but does not act as a significant mediating variable in the relationship between total assets and total debt on firm value. The direct effect of total assets on PBV is greater than the indirect effect through profitability, while total debt has a negative effect on PBV through its effect on net income.